Comparison of High-Resolution Manometry in Patients Complaining of Dysphagia Among Patients with or without Diabetes Mellitus - Immaneni, Shubha; Solanki, Arun; Annasamy, Chezhian; Karunakaran, Premkumar; Selvi, Caroline; A., Aravind; K, Muthukumaran; R., Murali (International Journal of Innovative Research in Medical Science, 2022)
Background: DM patients can have varying gastrointestinal symptoms. Assessment of esophageal dysmotility in diabetic patients using HRM has not been much evaluated. The aim of this study was to determine the motility pattern using HRM of Diabetics versus non-diabetics patients who presents with dysphagia. Methods: HRM of total 100 patients (48 diabetics and 52 non-diabetics) age and gender matched with dysphagia were included in this study. Patient’s demographic data, medication usage were recorded for each patient. HRM for each patient was done and parameters were recorded. Results: Overall 56% of diabetic patients were found to have an esophageal motility disorder. Diabetic patients were more likely to have ineffective esophageal motility (29% vs 7.7%, p = 0.005) as compared to non-diabetics. There was a trend for Achalasia and major disorders of peristalsis seen more in Non-diabetics patients with dysphagia as compared to Diabetic patients. Conclusions: More than half of the diabetic patients with dysphagia have some type of an esophageal motility disorder. Diabetic patients need to be assessed by HRM for motility disorder and requires proper glycemic control to prevent progression of dysphagia.